Histological and ultrastructural findings in a case of the Sézary syndrome - Labaze, J. J. (1972)
This paper deals with the histological and ultrastructural findings in a case of the Sézary syndrome. The striking nuclear and cytoplasmic features of the Sézary cell are illustrated, and the similarities of this cell to the mycosis fungoides cell are once more stressed.